G584(P) Sbar handover tool: improving maternity – paediatric communication at deliveries. (27th April 2015) - Sloper, E; Edmonds, C; Bailey, H; Lewis, L; Charlton, R
Abstract : Context: The project involves deliveries in our district general hospital delivery unit where a member of the paediatric team is requested to attend. The staff involved include midwives, neonatal nurses, paediatricians and obstetricians. Problem: Following the Root Cause Analysis (RCA) of a neonatal death at our hospital, it was recommended that improvements be made to delivery room handover between midwives and attending paediatricians. Currently handovers follow no specific pattern allowing for important information to be missed. As a result, the appropriate grade of paediatrician and correct equipment may not be present and paediatric staff may be ill-equipped to cope with the impending delivery. Assessment of problem and analysis of its causes: The RCA indicated that the condition of the baby at birth may have been predicted had the paediatrician been given a more detailed handover. A detailed handover may also have prompted them to call for senior support prior to delivery. Further discussion with paediatricians and midwives identified a lack of structure to these handovers, leaving babies at risk. Junior staff also felt that in stressful situations, prompts would ensure important information is remembered. Additionally, parents reported they would be reassured to observe a formal handover between teams. In other high-risk transfer areas, teams complete checklists to ensure they have the necessary information, staff and equipment to minimise risk. Currently, we have no such checklist for a paediatrician entering a delivery room. Handover relies on informal discussion, often whilst staff perform other tasks. It was therefore felt that a checklist would be a useful aide in prompting a concise, complete handover. Intervention: A search was conducted to find checklists for handover between midwifery and paediatric teams in other units but none could be identified. A checklist has therefore been designed by paediatricians and approved for this study. It covers the information necessary to provide safe initial care to a baby. The checklist has been attached to every resuscitaire in the delivery unit so it is easily accessible. Study design: The checklist was introduced to midwives and paediatricians through briefings at their daily handovers. The checklist was tested on a single day and tests of change made using a Plan, Do, Study, Act (PDSA) cycle. Following further feedback from all staff groups after 2 and 4 weeks, the checklist will be amended again. Strategy for change: The change has been implemented following briefings for staff and a trial of the checklist's use. It has been amended according to initial feedback and will be attached to all resuscitaires. Further feedback will be obtained at 2 and 4 weeks after formal introduction of the checklists and they will be updated accordingly. Once formalised, the checklists will be incorporated into midwifery teaching sessions and doctor's departmental induction programmes. Measurement of improvement: Analysis will be qualitative and will focus on staff satisfaction and suggested points for improvement. Parent satisfaction will be assessed via patient surveys. Quantitative assessment of delivery outcomes cannot be undertaken within this short timescale because the number of significant neonatal resuscitations is low. Effects of changes: It is hoped that there will be improved communication in the delivery unit resulting in better anticipation and safer care, fewer crash calls for middle grade paediatricians, higher levels of staff confidence and improved parent confidence in the staff caring for their baby. Lessons learnt: We hope to learn how to devise a safe means of communicating essential information between teams. Message for others: Safe handover is a GMC requirement for good practice and we have identified a high-risk area where there are no clear guidelines for this process. Implementing our checklist has allowed the process to be formalised, making delivery room handover safer, quicker and less liable to error.